The role of CITES in the conservation of marine fishes subject to international trade. Issue 4 (10th June 2013) - Vincent, Amanda C J; Sadovy de Mitcheson, Yvonne J; Fowler, Sarah L; Lieberman, Susan
Abstract All possible tools need to be marshalled for marine fish conservation. Yet controversy has swirled around what role, if any, the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) should play for marine fishes. This paper analyses the relevance and applicability of CITES as a complementary tool for fisheries management. CITES currently regulates the international trade of very few marine fish species, by listing them in its Appendices. After the first meeting of the Parties (member countries) in 1976, no new marine fish taxa were added to the CITES Appendices until 2002, when Parties agreed to act to ensure sustainable and legal international trade in seahorses (Hippocampus spp.) and two species of sharks. Progress has continued haltingly, adding only one more shark, humphead wrasse (Cheilinus undulatus) and sawfishes by 2012. Parties voice concerns that may include inadequate data, applicability of CITES listing criteria, roles of national fisheries agencies, enforcement challenges, CITES' lack of experience with marine fishes, and/or identification and by‐catch problems. A common query is the relationship between CITES and other international agreements. Yet all these arguments can be countered, revealing CITES to be a relevant and appropriate instrument for promoting sound marine fisheries management. In reality, Parties that cannot implement CITES effectively for marine fishes will also need help to manage their fisheries sustainably. CITES action complements and supports other international fisheries management measures. As CITES engages with more marine fish listings, there will be greater scope to analyse its effectiveness in supporting different taxa in different contexts.